The Impact of Price, Promotion, and Service Quality on Customer Satisfaction: The Mediating Role of Brand Image in Toyota Car Product - Saragih, Dea Agustia; Muharam, Hari (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
This study aims to analyze the effect of price, promotion, and service quality on customer satisfaction, with brand image serving as an intervening variable in Toyota car products in Sukabumi, West Java. Using a quantitative approach, this research employs a survey method involving Toyota customers as respondents. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and indirect relationships among variables. The results indicate that price, promotion, and service quality have significant positive effects on customer satisfaction. Furthermore, brand image mediates the relationship between these independent variables and customer satisfaction, demonstrating that a strong and positive brand perception enhances the overall satisfaction of customers. These findings emphasize the importance of consistent pricing strategies, effective promotional activities, and high-quality service delivery to strengthen brand image and sustain customer satisfaction. The implications of this research suggest that automotive companies, particularly Toyota dealers in Sukabumi, should focus on integrated marketing and service strategies to reinforce their competitive advantage and brand loyalty.